Greener Schoolyards, Greener Futures? Greener Schoolyards Buffer Decreased Contact With Nature and Are Linked to Connectedness to Nature - Luís, Sílvia; Dias, Ronisa; Lima, Maria Luísa (Frontiers in Psychology, 2020)
Children are spending less time in nature. They are not taking advantage of the benefits that are related to experiencing nature, such as the improvement of attentional capacity and stress reduction. Furthermore, they are also losing the opportunity to assess nature in a more positive way and to became more connected to nature, factors that appear to be fundamental to securing a greener future. To overcome this problem, researchers have been focusing on increasing children’s contact with nature in schools and in promoting garden-based learning programmes. Children spend most of their time in school, where they face many cognitive and relational demands. As such, schools might be the ideal context to increase children’s contact with nature with more empirical research being needed to understand the effects that greener schools might have. The goal of this study is to explore the effects of schoolyards in the children’s perceived restorativeness experiences, attitudes towards nature, connection to nature, and social competences. For that, we studied children (N = 132) from 3 elementary schools with different schoolyards: a school with cement yard with a few trees, a school with green areas, and a school where many parts of the yard were earthen and there was a vegetable garden that the students could cultivate as part of an ongoing garden-based learning programme. The results of a questionnaire confirmed that greener schoolyards related to stronger restorative experiences. As such, children might benefit from improving their attentional capacity during breaks. Unexpectedly, the perceived restorativeness effect was stronger for children who usually had lesser contact with nature than for children who contacted more with nature. This suggests that having schools with green yards might buffer some of the effects of reduced contacts with nature outside of school. Effects of the schoolyard in the children’s social competences did not appear to emerge. However, children that attended the school with the greener schoolyard had more positive attitudes and were more connected to nature than children from the other two schools. This further suggests that designing greener schoolyards might be an opportunity to contribute to reversing global environmental challenges.